Weighted Lebesgue and central Morrey estimates for $p$-adic multilinear Hausdorff operators and its commutators - Chuong, N. M.; Duong, D. V.; Dung, K. H. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 517.9We establish the sharp boundedness of $p$-adic multilinear Hausdorff operators on the product of Lebesgue and central Morrey spaces associated with both power weights and Muckenhoupt weights. Moreover, the boundedness for the commutators of $p$-adic multilinear Hausdorff operators on the such spaces with symbols in central BMO space is also obtained.